Foreign Direct Investment in Asean: The Moderating Role of Regulatory Quality on Macroeconomic Factors and Political Stability - April Kurniawan; Herry Subagyo; Ariati Anomsari (Ilomata International Journal of Management, 2026)
This study examines the determinants of Foreign Direct Investment (FDI) inflows in developing ASEAN countries, focusing on interest rates, exchange rates, inflation, and political stability, with regulatory quality as a moderating variable. Employing a quantitative, causal-comparative design, the study utilizes panel data from eight ASEAN countries (Malaysia, Thailand, Vietnam, Myanmar, Indonesia, Laos, the Philippines, and Cambodia) spanning the period from 2003 to 2023, sourced from the World Bank and the Worldwide Governance Indicators. Chow and Hausman tests indicate that the Fixed Effects Model provides the best fit for the data. The results indicate that interest rates have a negative and significant impact on FDI inflows, suggesting that higher borrowing costs deter foreign investors. Exchange rates exert a positive and significant influence, suggesting that currency depreciation enhances investment attractiveness. Inflation is found to be insignificant, indicating that investors can tolerate moderate inflation. Political stability shows a positive and significant effect, underscoring its crucial role in reducing investment risk and enhancing investor confidence. Furthermore, regulatory quality significantly moderates the effects of interest rates, exchange rates, and political stability on FDI. Strong regulatory frameworks can cushion the impact of adverse macroeconomic conditions and strengthen investment security. These findings extend institutional theory and emphasize the importance of macroeconomic, political, and regulatory stability in attracting FDI.